From the Crisis of Surplus Value to the Crisis of the Euro - Guglielmo Carchedi (World Review of Political Economy, 2012)
The financial crisis that erupted in 2007 and the subsequent crisis of the euro have received enormous attention both in the media and in specialized journals. One of the features of the recent literature is that the relation between Marx's law of the tendential fall in the rate of profit and the earthquake that has stricken the euro zone has been, with a few exceptions, overlooked. The basic reason for this failure is that it has become almost a matter of common sense to regard Marx's law as internally inconsistent and empirically disproved. What follows submits empirical material supporting the validity of the law. It then proceeds to sketch the basic lines of Marx's analysis of crises. Finally, it relates this analysis to the present financial turmoil and to the euro crisis.